From Hydroborations Catalyzed by Sn(II) Cations toPhotoluminescent Boronic Esters - Moždiak, Ondřej; Bíza, Tomáš; Střižík, Lukáš; Růžičková, Zdeňka; Erben, Milan; Dostál, Libor; Hupf, Emanuel; Jambor, Roman (Wiley, 2025)
The N-coordinated Sn(II) cations [{(2,6-iPr 2 -C 6 H 3 )-N = C(Me)-(6-MeO)-C 5 H 3 N}SnCl](SnCl3 ) (1), [{(2,6-iPr 2 -C 6 H 3 )-N = C(Me)-(6-P(O)(OiPr) 2 )-C 5 H 3 N}SnCl](SnCl3 ) (2), and [{(1,2-(C 5 H 4 N-2-CH = N) 2 CH 2 CH 2 )}SnCl](SnCl 3 ) (3) were prepared and usedas catalysts in the hydroboration of ketones and aldehydes.Mechanistic and kinetic studies provide evidence that theseelectrophiles interact with the C═O bond of the substratesand indicate a pseudo-first-order reaction with a rate con-stant of k = 70.2 h−1 using 2 mol% of 1. 1 could effectively beused as a catalyst in the hydroboration of a broad range ofsubstrates including, substituted benzaldehydes, heterocyclic carbaldehydes, and aliphatic aldehydes, as well as ketones.Finally, 1 was used in large-scale hydroboration reactions ofpyridine-substituted carbaldehydes to prepare the respectivepyridine-substituted boronic esters [2-(PinBOCH 2 )-C 5 H 4 N] (4), [2-(PinBOCH 2 )-4-(MeO)-C 5 H 3 N] (5), [2-(PinBOCH 2 )-6-(MeO)-C 5 H 3 N](6), [2-(PinBOCH 2 )-6-Br-C 5 H 3 N] (7), [2-(PinBOCH 2 )-5-Br-C5 H 3 N] (8),[3-(PinBOCH 2 )-C 5 H 4 N] (9), and borinate [2-[(BBN)OCH 2 ]-4-(MeO)-C 5 H 3 N] (10), which were characterized by NMR spectroscopy,single-crystal X-ray structure analysis, and an analysis of theirphotoluminescence.